influencia de la tribu urbana emo en adolescentes de edad comprendida entre 14 y 19 años en la ciudad de Loja, en el período febrero - septiembre del 2015 y la intervención del trabajador social - Espinosa Maldonado, Daniela Paola (2017)
Youth cultures are forms of youthful expression in which men and women con-struct and reconstruct their personal and collective subjectivities and identities; Through them, they incorporate and visualize ideologies, aesthetics and social and cultural expressions that grant loaded styles and meanings of their own, re-gardless of the dominant culture. Beyond stigmatizing and problematize the world of young people, the study ap-proaches the Emo youth culture in the city of Loja; where it is intended caress these groups, from the types of relationships, practices and dis-courses; at the same time, this research proposes, from a gender perspective, to recognize the juvenile condition from the places and roles that "play" or "assume" within the groupings. The advances of social behaviors are opening up inclusive spaces where we try to study and understand the reason for the existence of these human groups; however, it can’t be alien to the surrounding reality where they are taken as dif-ferent realities that cause negative entropy in society in general. For social and particularly intervention for social work is necessary this type of academic work, because they allow to build strategies for professional interven-tion, where young people are seen as subjects and actors of law, linked to a society and a territory; from here it is possible to incorporate reflection on the cultural in youth; achieving this occupies a central role in reading social problems, making this the object to our professional work. The profession of Social Worker seeks alternatives that create better days our society, taking it to the profession as a mobilizer of knowledge, assuming the task of actively participating in social daily life, construct proposals for intervention and execute them, which lead to social understanding and awareness of youth groups, where their membership allows them to build a new lifestyle without los-ing sight of values, without it our actions as social Workers will not have the de-sired success.